Impact of Behavioral Instructions in Language Models - Huamanchumo Trujillo, Francisco Gerardo (2024)
The impact of behavioral instructions on language models is a fundamental area of research in the field of processing for language that is human. This study focuses on analyzing how specific directions provided to language models affect their performance and efficiency on various tasks. It examines in detail the importance of instructions in the understanding for languages to be human and their influence on applications in activities such as machine translation, textual content creation, and document categorization. It discusses how behavioral instructions impact the configuration and training of models, as well as their predictive and generative capabilities. Concrete examples of how instructions can improve or limit the performance of linguistic models in different contexts are presented. The results obtained highlight the need to carefully consider behavioral instructions when developing and evaluating languages and their models, with the desire to optimize their accuracy and perform well on various linguistic tasks.